Conventional and reverse droop control in islanded microgrid: Simulation and experimental test - Villa, Alberto; Belloni, Federico; Chiumeo, Riccardo; Gandolfi, Chiara (2016 International Symposium on Power Electronics, Electrical Drives, Automation and Motion (SPEEDAM), 2016)
Local control of Distributed Energy Resources (DER) in microgrids usually relies on droop algorithm in order to ensure stability to the system in islanded operation. Conventional and reverse droop control are applied respectively to Voltage Control Mode (VCM) inverters and to Current Control Mode inverters (CCM). In low-voltage microgrid, traditional P-ω and Q-V droop characteristic is subject to the power coupling and could lead to unstable operating conditions due to dependence of load on the voltage and on the frequency. Therefore P-V and Q-ω droop characteristic, named resistive droop, is used in simulations and in experimental tests to show its effectiveness for a stable and decoupled regulation of islanded LV microgrid.